2017
DOI: 10.1177/2047487317695616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of switching from different treatment regimens to a fixed-dose combination pill (polypill) in patients with cardiovascular disease or similarly high risk

Abstract: Aims Cardiovascular fixed-dose combination pills, or polypills, may help address the widespread lack of access and adherence to proven medicines. Initiation of polypill-based care typically entails switching from current separately taken medications. Given the heterogeneity in usual care, there is interest in the impact of polypill treatment across different patterns of prior medication regimen. Methods A total of 2004 participants with established cardiovascular disease or estimated 5-year cardiovascular risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…This study provides evidence directly relevant to clinical implementation, contrasting with trial designs in which participants are prescribed the same medications as separate pills in the usual care group. In addition, participants were recruited regardless of baseline level or type of therapy, which again aids in assessment of treatment impact in real-life situations29 and is of particular importance when assessing the potential role of a polypill in reducing treatment gaps.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides evidence directly relevant to clinical implementation, contrasting with trial designs in which participants are prescribed the same medications as separate pills in the usual care group. In addition, participants were recruited regardless of baseline level or type of therapy, which again aids in assessment of treatment impact in real-life situations29 and is of particular importance when assessing the potential role of a polypill in reducing treatment gaps.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature is clear about the fact that polypills increase adherence to medication . Nonadherence to medication has been shown to be more prevalent in LMICs.…”
Section: Expected Benefits Of Polypills In Lmicsmentioning
confidence: 99%
“…The current literature is clear about the fact that polypills increase adherence to medication. [10][11][12][13][14][15][16][17][18][21][22][23] Nonadherence to medication has been shown to be more prevalent in LMICs. For instance, the PURE (Prospective Urban Rural Epidemiology) study demonstrated that in LMICs, only 3% of participants with a history of coronary heart disease or stroke were still taking drugs for secondary prevention of CVD 5 years post-event.…”
Section: From a Patient's Viewpointmentioning
confidence: 99%
See 2 more Smart Citations